Impact of Consumerism in the Project of Life: An Analysis Based on Civic Education - Ramírez-Díaz, Jose Laurian (Revista Electrónica Educare, 2016)
Nowadays, work is being considered a social fact through which people satisfy different types of needs. However, some lines of thought proposed consumption as sole mediator to achieve happiness, which promotes poor scenarios where some people jeopardize their health and integrity with excessive practices such as consumerism, causing effects of different nature such as environmental damage and alienation of the project of life. Civic education is facing major challenges regarding the inclusion of critical thinking in advertising messages, effective decision making, environmental conservation and protection, imitation of social models in a conscious way and appropriate stewardship.  This essay aims to treat these lines based on different theoretical edges concerning the human being concept and development; so they constitute training process criteria for analysis in different contexts, especially educational, whereas one of the Ministry of Public Education action policies is, precisely, civic training.